1983
DOI: 10.1159/000249845
|View full text |Cite
|
Sign up to set email alerts
|

Cimetidine and Chlorpheniramine in the Treatment of Psoriasis

et al.

Abstract: We examined the efficacy of cimetidine and chlorpheniramine alone and in combination in the treatment of psoriasis under the conditions of a randomised controlled double-blind study. Analysis of data from 52 patients revealed that none of the treatment regimes showed a demonstrable beneficial effect on the course of the psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In fact, several authors have reported a worsening of psoriasis after treatment.14,16, 17 However, in a recent long-term trial of ranitidine as treat¬ ment for psoriasis, in which six patients received a 4-month course of therapy, the lesions in four patients markedly im¬ proved and the lesions in two patients remained unchanged.18 Three of the four patients whose lesions improved experi¬ enced an initial deterioration of the disease. In fact, several authors have reported a worsening of psoriasis after treatment.14,16, 17 However, in a recent long-term trial of ranitidine as treat¬ ment for psoriasis, in which six patients received a 4-month course of therapy, the lesions in four patients markedly im¬ proved and the lesions in two patients remained unchanged.18 Three of the four patients whose lesions improved experi¬ enced an initial deterioration of the disease.…”
Section: Commentmentioning
confidence: 99%
“…In fact, several authors have reported a worsening of psoriasis after treatment.14,16, 17 However, in a recent long-term trial of ranitidine as treat¬ ment for psoriasis, in which six patients received a 4-month course of therapy, the lesions in four patients markedly im¬ proved and the lesions in two patients remained unchanged.18 Three of the four patients whose lesions improved experi¬ enced an initial deterioration of the disease. In fact, several authors have reported a worsening of psoriasis after treatment.14,16, 17 However, in a recent long-term trial of ranitidine as treat¬ ment for psoriasis, in which six patients received a 4-month course of therapy, the lesions in four patients markedly im¬ proved and the lesions in two patients remained unchanged.18 Three of the four patients whose lesions improved experi¬ enced an initial deterioration of the disease.…”
Section: Commentmentioning
confidence: 99%